Protestant Dublin, 1660-1760 - Usher, R. author. aut Link
X, 250 p.
Keywords: This innovative urban history of Dublin explores the symbols and spaces of the Irish capital between the Restoration in 1660 and the advent of neoclassical public architecture in the 1770s. The meanings ascribed to statues, churches, houses, and public buildings are traced in detail, using a wide range of visual and written sources.